Redesign UI/UX Aplikasi Access by KAI Menggunakan Metode Design Thinking - Abyan Muhammad Yassar; Isa Faqihuddin Hanif (LPPM Universitas Mulia, 2025)
This study discusses the redesign of the user interface (UI) and user experience (UX) on the Access by KAI application using the Design Thinking method to improve the application's usability. Data were obtained from 10 respondents through the distribution of the System Usability Scale (SUS) questionnaire using Google Form, and interviews were conducted to understand user experiences and needs. The initial usability evaluation showed an average score of 51, which is included in the poor category. Through five stages of Design Thinking: Empathize, Define, Ideate, Prototype, and Test, the researchers analyzed user needs, formulated problems, generated solutions, created prototypes, and conducted retesting. The test results after the redesign showed an increase in the SUS score to 72.5 in the good category. These findings prove that the Design Thinking approach is effective in understanding user problems and creating more optimal UI/UX solutions.